2017
DOI: 10.1007/s10549-017-4173-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Black breast cancer survivors with and without triple-negative breast cancer (TNBC)

Abstract: Purpose Black women are more likely to develop early onset (≤50 years) breast cancer (BC) and have the lowest five-year, cause-specific survival rate of any United States (U.S.) racial or ethnic group. These disparities can be attributed partially to the higher rate of triple negative BC (TNBC) in Blacks. Yet, little is known about health-related quality of life (HRQOL) among Black women with TNBC. Methods Black women with invasive BC ≤50 years were recruited via the Florida State Cancer Registry as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…The onset of race-group mortality rate disparities coincides with the advent of hormone-targeted therapies [5] that are now standard-of-care for hormone receptor-positive tumors. Compared to women of European descent, AA women [4,[6][7][8][9][10][11][12][13] and women of African descent world-wide [9,[14][15][16] have a higher incidence of triple-negative breast cancer (TNBC) [17][18][19][20][21], which is characterized by the absence of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). Therefore, in the context of standardizing ER/PR-and HER2-targeted therapies, the divergence of AA vs. EA mortality likely unmasked population-level differences in tumor biology, which we have previously shown to correlate with genetic ancestry [22].…”
Section: Introductionmentioning
confidence: 99%
“…The onset of race-group mortality rate disparities coincides with the advent of hormone-targeted therapies [5] that are now standard-of-care for hormone receptor-positive tumors. Compared to women of European descent, AA women [4,[6][7][8][9][10][11][12][13] and women of African descent world-wide [9,[14][15][16] have a higher incidence of triple-negative breast cancer (TNBC) [17][18][19][20][21], which is characterized by the absence of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). Therefore, in the context of standardizing ER/PR-and HER2-targeted therapies, the divergence of AA vs. EA mortality likely unmasked population-level differences in tumor biology, which we have previously shown to correlate with genetic ancestry [22].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, survivors with negative hormone and HER-2 (those with triple-negative breast cancer) may have relatively poor prognoses; thus, a study of survivors of triple-negative breast cancer found that they experienced significantly greater emotional distress and worry about their cancer than those who were diagnosed with a non-triple-negative breast cancer. [ 31 ] This finding, we suggest, may help to explain why, in this study, the survivors who received targeted therapy reported better sleep quality than those who received nontargeted therapy.…”
Section: Discussionmentioning
confidence: 65%
“…Com relação à sobrevivência, é imprescindível assinalar que Samuel et al (2016), Pinheiro et al (2016), Pinheiro et al (2017), Vadaparampil et al (2017) e Claridy, Ansa, Damus, Alema-Mensah e Smith (2018) não concordaram quanto aos parâmetros temporais referentes a essa etapa da experiência oncológica. Seus estudos acataram desde o período de recebimento do diagnóstico até um período indeterminado que pode ser confundido com o próprio ciclo vital da paciente.…”
Section: Resultsunclassified